PERAN PENYULUH PERTANIAN DALAM PENUMBUHAN GABUNGAN KELOMPOK TANI (GAPOKTAN) DI DESA PERMANU KECAMATAN PAKISAJI KABUPATEN MALANG - Amantur, Leonardus; Suwasono, Son; Khoirunnisa', Ninin (Fakultas Pertanian, 2018)
This study aims to (a) examine the role of agricultural extensionists in the growth of Combined Farmer Groups (b) to examine the impact of agricultural extension role in the growth of the Combined Farmer Group. research method that is done include taking samples by using random sampling method. Data collection is taken primary data and secondary data. Data analysis used descriptive (Qualitative) that is with skorin. Based on the results of research in Permanu Village Pakisaji District of Malang can be concluded that: The role of Agricultural Extension Farmers in the combined growth of Madukismo farmer groups in Permanu Village is fairly good, judging from the respondents' answers Joint group members 71.4% of respondents who answered well. The impact of the role of agricultural extension in the growth of Gapoktan Madukismo in Permanu Village has increased with the involvement of agricultural extension workers. Penelitian ini bertujuan untuk (a) mengkaji peran penyuluh pertanian dalam penumbuhan Gabungan Kelompok Tani (b) mengkaji dampak peran penyuluh pertanian dalam penumbuhan Gabungan Kelompok Tani. Metode penelitian yang dilakukan meliputi pengambilan sampel dengan menggunakan metode acak random sampling. Pengumpulan data diambil data primer dan data skunder. Analisis data yang digunakan deskriptif (Kualitatif) yaitu dengan skorin. Berdasarkan hasil penelitian dapat disimpulkan bahwa : Peran Penyuluh Pertanian Lapang dalam penumbuhan gabungan kelompok tani Madukismo di Desa Permanu terbilang baik, dilihat dari jawaban responden anggota Gabungan kelompok tani sebesar 71,4% responden yang menjawab baik. Dampak peran penyuluh pertanian dalam penumbuhan Gapoktan Madukismo di Desa Permanu mengalami peningkatan dengan adanya keterlibatan penyuluh pertanian.